THE APPLICATION OF BLOCKCHAIN TECHNOLOGY FOR ISSUING AND VERIFYING TAMPER-PROOF DIGITAL CREDENTIALS IN A LIFELONG HYBRID LEARNING SYSTEM - Fatima Malik; ahmed shah; Nathaniel Ramos; Isabel Martinez (Yayasan Adra Karima Hubbi, 2025)
The rapid expansion of lifelong and hybrid learning ecosystems has amplified the need for secure, verifiable, and portable academic credentials. Conventional credentialing systems are prone to data breaches, document forgery, and verification delays, which compromise institutional integrity and learner mobility. Blockchain technology offers a decentralized solution for issuing and validating tamper-proof digital credentials that ensure data immutability, transparency, and learner ownership. This study aims to design and evaluate a blockchain-based credentialing framework integrated within a lifelong hybrid learning system, providing a secure, interoperable, and scalable model for educational institutions. The research employed a design-based approach combining system architecture modeling and pilot testing in three Indonesian universities. Data were collected through usability testing, stakeholder interviews, and system performance metrics. The findings revealed that the blockchain credentialing model enhanced verification efficiency by 63%, reduced administrative errors by 41%, and improved trust perception among employers and learners. The smart contract mechanism automated credential issuance, while decentralized verification protocols ensured authenticity without reliance on centralized databases. The results confirm that blockchain-based digital credentials can strengthen academic credibility and facilitate global recognition of hybrid learning achievements. The study concludes that blockchain integration in education not only promotes transparency and trust but also aligns with the principles of lifelong learning and digital sovereignty. Future implementations should explore interoperability across cross-border educational systems and adaptive governance models for data privacy and regulatory compliance.